High Impulse Voltage and Current Measurement Techniques c y Klaus Schon. - Schon, Klaus; SpringerLink (Online service) (Heidelberg : Springer International Publishing : Imprint: Springer, 2013)
Equipment to be installed in electric power-transmission and distribution systems must pass acceptance tests with standardized high-voltage or high-current test impulses which simulate the stress on the insulation caused by external lightning discharges and switching operations in the grid. High impulse voltages and currents are also used in many other fields of science and engineering for various applications. Therefore, precise impulse-measurement techniques are necessary, either to prevent an over- or understressing of the insulation or to guarantee the effectiveness and quality of the application. The book deals with: principal generator circuits for generating high-voltage and high-current impulses measuring systems and their calibration according to IEC 60060 and IEC 62475 methods of estimating uncertainties of measurement mathematical and experimental basis for characterizing the transfer behavior of spatially extended systems used for measuring fast transients. This book is intended for engineers and technicians as well as students of high-voltage engineering and electrical power supply systems.
Characterisation and Generation of High Impulse Voltages and Currents -- Representation of Impulses in Time and Frequency Domain -- Transfer Behaviour of Linear Systems and Convolution -- Digital Recorder, Impulse Voltmeter and Impulse Calibrator -- Measurement of High-Voltage Impulses -- Measurement of High-Current Impulses -- Calibration of the measuring systems -- Evaluation of Uncertainties of Measurement.
Keywords: Engineering; System safety; Production of electric energy or power; Electric engineering; Engineering; Power Electronics, Electrical Machines and Networks; Energy Technology; Quality Control, Reliability, Safety and Risk